2018
DOI: 10.1098/rsos.170868
|View full text |Cite
|
Sign up to set email alerts
|

Development of bioabsorbable polylactide membrane with controllable hydrophilicity for adjustment of cell behaviours

Abstract: Cell functions can be mediated through their interactions with the microenvironments, which highly depend on the surface state of the substrate. However, how to finely adjust the surface of biomaterials is still very challenging. In this study, poly(d,l-lactide) (PDLLA) with high molecular weight was synthesized via ring opening polymerization, which was hot-pressed into PDLLA membrane. In order to modify the hydrophobicity of the membrane (a limiting factor for its biomedical application), an amphiphilic mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…Studies have shown that membranes with a WCA ranging from 40° to 60° may be appropriate for cell adhesion, 49 and optimized cell adhesion can be achieved on the modified membrane with a contact angle of around 50°. 50,51 In our study, the results of cell proliferation and morphology indicated that the obtained C-PCL/CS/MET membranes with a WCA of 44.25 ± 1.37° would be more suitable for BMSCs growth.…”
Section: Resultsmentioning
confidence: 54%
“…Studies have shown that membranes with a WCA ranging from 40° to 60° may be appropriate for cell adhesion, 49 and optimized cell adhesion can be achieved on the modified membrane with a contact angle of around 50°. 50,51 In our study, the results of cell proliferation and morphology indicated that the obtained C-PCL/CS/MET membranes with a WCA of 44.25 ± 1.37° would be more suitable for BMSCs growth.…”
Section: Resultsmentioning
confidence: 54%
“…1 a). PLLA offered a chemical shift at δ = 1.56 ppm corresponding to methyl group on the polymer chain, and a chemical shift at δ = 5.16 ppm related to the methylene group on the polymer framework, indicating a successful synthesis of PLLA polymer [ 32 ]. Gel penetration chromatography (GPC) is a common method for molecular weight measurement of polymers.…”
Section: Resultsmentioning
confidence: 99%
“…The surface characteristics of materials, including surface hydrophilicity and charges, have a significant impact on cell behaviors [ 39 , 40 ]. In this case, the hydrophobicity of PLLA polymer greatly limits its biomedical application [ 32 ]. The hydrophilicity of PLLA and PNA-doped nanofibrous membranes was evaluated using a water contact angle test at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, cell adhesion and proliferation were found to t into the scaffold of PEG-1, but not that of PEG-2. It has been suggested that scaffolds are conducive to cell adhesion when the contact angle ranges from 40 to 60 , 34,35 and the water contact angle of the PEG-2 group was outside that range.…”
Section: Discussionmentioning
confidence: 99%